Changing Pattern of Bacteriological Profile, Antimicrobial Resistance and Mortality in Neonatal Sepsis in a Developing Country: A Retrospective Study - Saha, Anindya Kumar; Tiwari, Abhishek Kumar; Chattopadhyay, Pinaki; Mukherjee, Suchandra; Saha, Bijan (Journal of Nepal Paediatric Society, 2021)
Introduction: Neonatal sepsis is one of the major contributors of mortality and morbidity among neonates. Irrational and overuse of antibiotics have led to an increase in antimicrobial resistance. This study was undertaken to investigate the bacteriological profile, antimicrobial resistance and predictors of mortality among blood culture-positive cases of neonatal sepsis. Methods: Demographic and bacteriological data were collected from electronic and manual case records. Automated BACTEC 9050 system using Peds Plus Vial was used for blood culture. Multidrug resistance was defined as a resistance to any three of five antibiotic classes like aminoglycoside, carbapenem, extended spectrum cephalosporins, fluoroquinolones and piperacillin. Results: Among 7180 admitted neonates, 433 (6.03%) were blood culture positive with early onset sepsis (EOS) in 50.1% of cases. Gram negative bacteria was the causative organism in 371 (85.7%) babies with klebsiella being the commonest pathogen (43.6%). The pathogen mix of early onset and late onset sepsis was similar and 90% of gram negative isolates were resistant to penicillin group. Multi drug resistance (MDR) was found in 51.2% of the gram negative organisms. EOS (Odds ratio 1.99; 95% confidence interval, 1.29-3.05) and MDR (Odds ratio 2.07; 95% confidence interval, 1.77-4.12) were independently associated with neonatal death due to sepsis. Conclusions: Gram-negative pathogens, specifically klebsiella accounted for a huge burden of neonatal sepsis. EOS and MDR were found to be independent predictors of death due to such sepsis. This study calls for multicentric studies on early onset neonatal infection and its relationship with pathogenic maternal flora.